Peran Kantor Urusan Agama (KUA) dalam Meminimalisir Pernikahan Dini (Studi Kasus di Kabupaten Pangkep) - Zulfadli Zulfadli (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2023)
The purpose of this study is to find out the extent of the role of the Office of Religious Affairs in suppressing the increase in Early Marriages, then outlined in several research problems, namely how the role of Office of Religious Affairs in Minimizing Early Marriage in Pangkep Regency and the impact caused. This research is a qualitative research with a sociological juridical approach. The results of this study explain the efforts of the Office of Religious Affairs in minimizing Early Marriage, namely socializing the Change of Laws Republic of Indonesian about marriage, explaining about the impact caused, take an individual approach, provide understanding of religion and law to the community and the impacts caused by Early Marriage in Pangkep Regency, namely social impacts, economic impacts, psychological impacts, reproductive health impacts and increasing divorce rates.